Using electronic resourses when delivering the module of mineralogy and petrography in English as a way to motivate students (as illustrated by blogging); Education and New Learning Technologies, EDULEARN 16 - Lutoshkina O. S. Olga Sergeevna; Zabrodina I. K. Irina Konstantinovna; Cherkasova T. Yu. Tamara Yurievna; Slesarenko I. V. Inga Valerievna (2016, 2016)
Title screen